2023
DOI: 10.1371/journal.pone.0281310
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of non-communicable diseases among Ghanaian adults: A survey at a secondary healthcare level

Abstract: The current epidemiological transition of diseases in Ghana necessitates understanding their burden and the associated context-specific risk factors to inform disease prevention strategies. To determine the prevalence and determinants of selected Non-Communicable Diseases (NCDs) among patients seeking healthcare services in a secondary health facility in Ghana. A facility-based survey was conducted among adult patients 18 years and above between May and July 2021, using a multi-stage sampling approach. Data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The high burden of NCDs in LMICs is consistent with the increasing prevalence of chronic NCD health outcomes. In Ghana, for example, research has shown a prevalence rate of 26.7% among a sample of Ghanaians with a mean age as low as 38 years [2]. A recent study using nationally representative data found hypertension prevalence to be as high as 29.7% [3].…”
Section: Introductionmentioning
confidence: 99%
“…The high burden of NCDs in LMICs is consistent with the increasing prevalence of chronic NCD health outcomes. In Ghana, for example, research has shown a prevalence rate of 26.7% among a sample of Ghanaians with a mean age as low as 38 years [2]. A recent study using nationally representative data found hypertension prevalence to be as high as 29.7% [3].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, NCDs account for the majority of all-cause mortality in Ghana, with major NCDs such as heart diseases, strokes, diabetes, cancers and respiratory diseases dominating outpatient departments [ 8 ]. In Accra, about one-fourth of out-patient clients had an NCD [ 9 ] and about 5% of homeless residents had diabetes [ 10 ]. Despite the rising burden of NCD morbidity and mortality, awareness, treatment, and control of NCDs have remained critically low [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study further concluded that more than half (54%) were physically inactive and the odds of developing NCDs were higher in females. 16 If current trends continue, it is projected that NCDs would exceed all other causes of mortality in Ghana by 2030 and in Africa by 2035. 17 Many non-communicable diseases, such as cardiovascular disease and diabetes, have also been linked to sedentary behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Boakye et al 16 indicated that the overall prevalence of the certain non-communicable diseases was 26.7% (CI = 0.23–0.31), of which hypertension (22.7%) was the most prevalent. The study further concluded that more than half (54%) were physically inactive and the odds of developing NCDs were higher in females.…”
Section: Introductionmentioning
confidence: 99%